Enhancement of temporal resolution using improved time-variant spectral whitening - Diako Hariri Naghadeh (2018)
© 2017 Sinopec Geophysical Research Institute. Time-variant spectral whitening was introduced as a powerful method to enhance temporal resolution. Despite all the benefits the method carries, some negative points include balancing all kinds of amplitudes and affecting high reflections that show the effect of fluids or lithology changing and creating a Gibbs phenomenon when the objective is to enhance resolution. Synthetic and real data sets were used to highlight those weaknesses and some new steps were added to the methodology to improve and overcome the problems. The improved technique can whiten the spectrum more without sacrificing or touching high reflection amplitudes. To apply this method large Gaussian windows were shifted. These windows had frequency bandwidths equal to 70 Hz. An overlap of 90% between subsequent windows was chosen to extract the frequency components. The gain function for each component was measured from the inverse of an area-based envelope. Summation of the product of each frequency component with its own gain function achieves an enhanced trace. Comparison of the rms amplitude attributes computed from the general method and from our improved method shows that the general time-variant spectral whitening decreases the levels of high amplitudes and boosts low amplitudes considerably, which makes differentiation between amplitudes impossible.